SUPER NATIVE CHICKEN (Gallus gallus domesticus), AND PADDY SNAIL AS A MIXTURE OF RATIONS - Raga Samudera; Achmad Jaelani; Muhammad Syarif Djaya; Muhammad Irwan Zakir; Gusti Khairun Ni'mah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Super native chicken (Gallus gallus domesticus), and paddy snail as a mixture of rations, Super native chicken is a cross between native chicken and red laying hen, which is given the ration contains paddy snail flour. And the parameters of research against appearance consisting of ration consumption, final body weight and ration conversion. Design used Complete Random Design (RAL) with five treatments and four replications, such treatment is ; TK0 (0% paddy snail flour),  TK5 (5% paddy snail flour),  TK10 (10% paddy snail flour),  TK15 (15% paddy snail flour),  TK20 (20% paddy snail flour),  From the results of the research can be stated that all parameters (ration consumption, final body weight and ration conversion shows real influence, It is recommended to use up to 15% paddy snail flour in the ration of super nitive chicken.